Selective CB2 receptor agonists. Part 3: The optimization of a piperidine-based series that demonstrated efficacy in an in vivo neuropathic pain model. Issue 3 (1st February 2015) - Bartolozzi, Alessandra; Cirillo, Pier Francesco; Berry, Angela K.; Hickey, Eugene R.; Thomson, David S.; Wu, Lifen; Zindell, Renee; Albrecht, Claudia; Ceci, Angelo; Gemkow, Mark J.; Nagaraja, Nelamangala V.; Romig, Helmut; et al.
Graphical abstract